Peripheral decarboxylase inhibitors paradoxically induce aromatic L-amino acid decarboxylase - Anouke van Rumund (Nature Portfolio, 2021)
Abstract Peripheral decarboxylase inhibitors (PDIs) prevent conversion of levodopa to dopamine in the blood by the enzyme aromatic L-amino acid decarboxylase (AADC). Alterations in enzyme activity may contribute to the required higher dosages of levodopa observed in many patients with Parkinson’s disease. We evaluated the effect of levodopa/PDI use on serum AADC enzyme activity. Serum AADC enzyme activity was evaluated in three independent cohorts of patients with Parkinson’s disease or parkinsonism (n = 301) and compared between patients on levodopa/PDI vs. patients not on this medication. AADC enzyme activity was elevated in 62% of patients on levodopa/PDI treatment, compared to 19% of patients not on levodopa/PDI (median 90 mU/L vs. 50 mU/L, p < 0.001). Patients with elevated AADC activity had longer disease duration and higher doses of levodopa/PDI. These findings may implicate that peripheral AADC induction could underlie a waning effect of levodopa, necessitating dose increases to maintain a sustained therapeutic effect.